How nations remember a narrative approach - Wertsch, James V. 1947- (Oxford University Press, 2021)
Different Memories, Different Worlds -- A Conceptual Tool Kit -- National Narratives -- Selectivity and Emplotment in National Memory -- Narrative Dialogism in National Memory -- Managing National Memory
Includes bibliographical references and index
Keywords: Kollektives Gedächtnis; Narrativ -- Sozialwissenschaften; Geschichtsbewusstsein; Geschichtspolitik; Nation; Nationalismus; Nationalism / Psychological aspects; Collective memory; International relations